(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
Permanent Magnet Synchronous Motor (PMSM) is an AC motor in which the rotor must operate at synchronous speed in all load conditions. If the motor mechanical load increases, the motor can lose synchronization, stopping the motor. In sensorless control systems, i.e., those without speed sensors, the speed is estimated from the stator current using the Model Reference Adaptive System (MRAS) algorithm. Because such systems therefore cannot detect the loss of synchronization, it is necessary to design a synchronization loss detection system. Here, another speed estimation calculated from the stator currents and voltages is introduced. The speed is called a calculated speed. In the normal condition (synchronous condition), estimated speed and calculated speed will be approximately equal. However, when synchronization loss occurs, these two speed values diverge. On the basis of this phenomenon, a synchronization loss detection algorithm and method are developed. The algorithm’s speed-delta boundary values and detection period must be determined. The greater the setpoint speed, the higher the speed-delta boundary values but the smaller the detection period. The experiments confirm that the proposed algorithm is able to effectively detect the occurrence of synchronization loss.